How Do We Look? : Resisting Visual Biopolitics - Rony, Fatimah Tobing (Book collections on Project MUSE., 2021)
"Fatimah Tobing Rony draws on the transnational visual images of Indonesian women as a way to theorize what she calls visual biopolitics-the ways visual representation determines which lives are made to matter more than others"--